Surprising efficacy twist of two established cytostatics revealed by a-la-carte 3D cell spheroid preparation protocol - Kroupová, Jiřina; Hanuš, Jaroslav; Štěpánek, František (European journal of pharmaceutics and biopharmaceutics, 2022)
Three-dimensional cell culture systems are increasingly used for biological and anticancer drug screening as they mimic the structure and microenvironment of tumors more closely than conventional two-dimensional cell models. In this study, the growth kinetics of colon adenocarcinoma-derived spheroids (HT-29 cell line) cultivated in liquid marble micro-bioreactors and nonadherent PDMS-coated well plates was investigated in detail and enabled precise control of the spheroid size by the seed cell density and cultivation time. The therapeutic effect of 5-fluorouracil and irinotecan hydrochloride in 2D monolayer cell culture and 3D tumor spheroids revealed an unexpected twist in their efficacy due to different ability to penetrate through 3D microtissue. For 5-fluorouracil, the inhibitory concentration IC50 after 48 h exposure increased from 11.3 µM for a 2D cell culture to 707.7 µM for a 3D spheroid. In the case of irinotecan, IC50 increased from 24.9 µM to 77.8 µM. Despite its higher molar weight, irinotecan appeared to penetrate the 3D spheroid structure more efficiently than 5-fluorouracil. While 5-fluorouracil mainly caused a suppression of spheroid growth from the outside, irinotecan affected the entire spheroid and caused its originally compact structure to disintegrate. The acquired results highlight the need to screen cancer chemotherapeutics on 3D tumor models, as contrasting results can be obtained compared to standard 2D cell cultures.
Keywords: buněčné sféroidy; Tumor Microenvironment; Spheroids, Cellular; nádorové buněčné linie; nádorové mikroprostředí; Polydimethylsiloxane; fluoruracil; Fluorouracil; adenokarcinom; Cell Line, Tumor; Irinotecan; 5-Fluorouracil; Cytostatic Agents; nádory tračníku; cytostatické látky; Humans; Irinotecan hydrochloride; irinotekan; 3D Cell cultures; Colonic Neoplasms; Liquid marbles; Adenocarcinoma; Tumor spheroids; lidé